Hollow porous positive electrode material precursor and preparation method thereof and lithium ion battery

By depositing composite metal hydroxide on the surface of the aminated carbon microspheres and removing the template, hollow porous positive electrode material precursor was prepared, which solved the agglomeration and twinning problems in traditional methods, and improved the discharge capacity and mechanical strength of the material.

CN119284989BActive Publication Date: 2025-03-25YIBIN GUANGYUAN LITHIUM BATTERY MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411814714.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-25
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

When preparing the precursor of the ternary positive electrode material by traditional co-precipitation method, the initial direct nucleation method can easily lead to secondary pellet aggregation and twinning, affecting the performance stability and controllability of the material.

Method used

Aminated carbon microspheres are used as templates to deposit composite metal hydroxide on their surface, and then mixed with the hydroxylation reagent solution to react. After washing and drying, the internal template is removed by high temperature to obtain a hollow porous positive electrode material precursor.

Benefits of technology

The lithium ion propagation path is shortened through the hollow porous structure, the discharge capacity and energy density are improved, and the mechanical strength is strengthened by adjusting the shell process to ensure the stability of the material during the charging and discharging process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284989B_ABST
    Figure CN119284989B_ABST
Patent Text Reader

Abstract

The present invention discloses a hollow porous cathode material precursor, a preparation method thereof and a lithium ion battery. The hollow porous cathode material precursor provided by the present invention comprises a hollow core and a porous shell, and the surface of the porous shell contains hydroxyl groups. The core of the hollow porous cathode material precursor has a highly hollow structure, and the shell has a large number of highly open three-dimensional pores, which can shorten the lithium ion propagation path to a certain extent, and can improve the discharge capacity and energy density at the hollow porous cathode material end. In addition, after the surface of the porous shell is modified by hydroxylation, the metal active sites can be increased, and the insertion and extraction of lithium ions can be enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a hollow porous positive electrode material precursor and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, no memory effect, low self-discharge rate, and no pollution. Compared with other types of batteries, they are safer and more environmentally friendly. As a high-performance, environmentally friendly battery type, they have broad application prospects.

[0003] Ternary cathode material is one of the commonly used cathode materials in lithium-ion batteries, usually referring to lithium nickel manganese cobalt oxide. Compared with traditional cathode materials such as lithium cobalt oxide (LCO) and lithium manganese oxide (LMO), ternary cathode materials have better cycle stability and can still maintain high capacity and performance after multiple charge and discharge cycles. Ternary cathode materials have high energy density and can provide relatively high energy storage, and the manganese and cobalt elements in them give them high thermal stability and safety. In general, ternary cathode materials have many advantages such as high energy density, good cycle life, excellent thermal stability, high safety and environmental protection, making them one of the widely used cathode materials in lithium-ion batteries. With the continuous improvement of technology and the expansion of application fields, ternary cathode materials are expected to continue to play an important role in the future.

[0004] Common methods for preparing ternary precursors include the following:

[0005] (1) Precipitation method: An appropriate amount of nickel, manganese and cobalt salt solution is introduced into a reactor together with a precipitant and a complexing agent. The resulting precipitate is washed, dried, demagnetized, and other steps to obtain a ternary precursor.

[0006] (2) Solid-phase reaction method: A mixture of nickel, manganese, cobalt salts and an appropriate amount of carbonate is subjected to a high-temperature solid-phase reaction to generate a ternary precursor.

[0007] (3) Sol-gel method: Through the sol-gel process, the metal salt and dopant are dissolved into a sol, which is then gelled to form a gel, and finally calcined to obtain a ternary precursor.

[0008] Among them, the coprecipitation method is relatively simple and easy to operate compared to other synthesis methods, and is suitable for large-scale production. The ternary precursor synthesized by the coprecipitation method has a low impurity content, which is beneficial to the performance of subsequent materials. At the same time, the morphology and size of the precursor can be controlled during the preparation process to prepare uniform particles or structures, which is beneficial to the performance stability and controllability of the material. However, the direct nucleation method in the early stage of the traditional coprecipitation method often leads to secondary ball agglomeration and twinning. Summary of the invention

[0009] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a hollow porous positive electrode material precursor and a preparation method thereof and a lithium ion battery.

[0010] The present invention solves the technical problem by adopting the following technical solutions.

[0011] The invention provides a hollow porous positive electrode material precursor. The hollow porous positive electrode material precursor comprises a hollow core and a porous shell, and the surface of the porous shell contains hydroxyl groups.

[0012] The present invention also provides a method for preparing the above-mentioned hollow porous positive electrode material precursor, comprising the following steps: using amino carbon microspheres as templates, depositing composite metal hydroxides on the surfaces of the amino carbon microspheres to obtain a reaction slurry, then mixing the reaction slurry with a hydroxylation reagent solution for reaction, washing and drying, and then removing the internal template by high temperature to obtain a hollow porous positive electrode material precursor.

[0013] The present invention also provides a hollow porous positive electrode material, which is prepared by mixing and sintering the above hollow porous positive electrode material precursor or the hollow porous positive electrode material precursor prepared by the above preparation method with a lithium source.

[0014] The present invention also provides a lithium ion battery, which comprises the hollow porous positive electrode material.

[0015] The present invention has the following beneficial effects:

[0016] The present invention provides a hollow porous cathode material precursor and a preparation method thereof and a lithium ion battery. The hollow porous cathode material precursor includes a hollow core and a porous shell, and the surface of the porous shell contains hydroxyl groups. The core of the hollow porous cathode material precursor has a highly hollow structure, and the shell has a large number of highly open three-dimensional pores, which can shorten the lithium ion propagation path to a certain extent, and can improve the discharge capacity and energy density at the hollow porous cathode material end. At the same time, the mechanical strength of the shell can be strengthened by adjusting the shell process, so that its hollow structure can be inherited during the high-temperature lithiation process, and it can have sufficient mechanical strength in the electrical performance cycle test, ensuring that the hollow porous cathode material will not crack due to charging and discharging. At the same time, after the surface of the porous shell is modified by hydroxylation, the metal active sites can be increased to enhance the insertion and extraction of lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 The scanning electron microscope image (left) and the scanning electron microscope cross-sectional image (right) of the product obtained in Example 1 are shown;

[0019] Figure 2 The following are the scanning electron microscope images (left) and scanning electron microscope cross-sectional images (right) of the product obtained in Comparative Example 1;

[0020] Figure 3 The scanning electron microscope image (left) and the scanning electron microscope cross-sectional image (right) of the product obtained in Comparative Example 2 are shown;

[0021] Figure 4 The following are the scanning electron microscope image (left) and scanning electron microscope cross-sectional image (right) of the product obtained in comparative example 3. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0023] A hollow porous cathode material precursor, a preparation method thereof, and a lithium-ion battery provided in an embodiment of the present invention are described in detail below.

[0024] In a first aspect, an embodiment of the present invention provides a hollow porous cathode material precursor, wherein the hollow porous cathode material precursor comprises a hollow core and a porous shell, and the surface of the porous shell contains hydroxyl groups.

[0025] The embodiment of the present invention provides a hollow porous cathode material precursor, which is a new hollow structure precursor, consisting of an inner hollow and an outer shell with greater mechanical strength. The inner core of the hollow porous cathode material precursor has a highly hollow structure, and the outer shell has a large number of highly open three-dimensional pores, which can shorten the lithium ion propagation path to a certain extent, and can improve the discharge capacity and energy density at the hollow porous cathode material end. At the same time, the mechanical strength of the shell can be strengthened by adjusting the shell process, so that its hollow structure can be inherited during the high-temperature lithiation process, and it can have sufficient mechanical strength in the electrical performance cycle test to ensure that the sphere will not crack due to charging and discharging.

[0026] In an optional embodiment, the hollow core of the hollow porous positive electrode material precursor is a hollow spherical structure, and D50 is 0.2 μm-0.8 μm, and the thickness of the porous shell is 2.2 μm-3.8 μm.

[0027] In an optional embodiment, the porosity of the porous shell is 10%-50%, and the mass of the porous shell containing hydroxyl groups accounts for 20%-60% of the total mass of the hollow porous positive electrode material precursor.

[0028] In the second aspect, an embodiment of the present invention also provides a method for preparing the above-mentioned hollow porous positive electrode material precursor, comprising the following steps: using amino carbon microspheres as templates, depositing composite metal hydroxides on the surface of the amino carbon microspheres to obtain a reaction slurry, and then mixing the reaction slurry with a hydroxylation reagent solution for reaction, washing and drying, and then removing the internal template by high temperature to obtain a hollow porous positive electrode material precursor.

[0029] The embodiment of the present invention also provides a method for preparing the above-mentioned hollow porous cathode material precursor. The inventors start from the structure of the precursor from the aspects of reducing costs and facilitating mass production, and design a cathode material precursor with a hollow structure. Specifically: Aminated carbon microspheres are selected as templates, and the excellent chemical properties of amino functional groups (such as high electron donation and good nucleophilicity) are used to act as a convenient connection base between aminated carbon microspheres and metal ions, so that the ternary or quaternary salt solution is deposited on the surface of the aminated carbon microspheres after feeding, without additional nucleation. In addition, the aminated carbon microspheres can support the hollow structure of the quaternary or ternary precursors. Compared with other hollow structure precursors, the structure is more stable and there is no structural collapse problem. In the subsequent high-temperature removal process, the high temperature can decompose the template in the center, and the template agent passes through the outer shell during volatilization, and a large number of pore structures can be formed in the shell layer to obtain a cathode material precursor with a hollow porous structure. The above structure can shorten the lithium ion propagation path and improve the discharge first effect and discharge capacity.

[0030] It should be noted that the preparation method of the hollow porous positive electrode material precursor provided in the embodiment of the present invention and the preparation method of the amino carbon microspheres used can be referred to patent CN202310376633.1, a method for preparing a water-based amino baking varnish.

[0031] In an optional embodiment, the steps include: adding a mixed salt solution, a precipitant solution and a chelating agent solution to a base liquid containing amino carbon microspheres, depositing a composite metal hydroxide on the surface of the amino carbon microspheres to obtain a reaction slurry, then mixing the reaction slurry with a hydroxylating agent solution for reaction, centrifugally dehydrating and drying, and then removing the internal template by high temperature to obtain a hollow porous positive electrode material precursor.

[0032] In an optional embodiment, the preparation of the reaction slurry includes: continuously and concurrently flowing a mixed salt solution, a precipitant solution and a complexing agent solution into a bottom solution, adjusting the flow rate of the precipitant solution and the complexing agent solution to stabilize the reaction atmosphere according to the test situation, and continuously reacting until a reaction slurry of a desired particle size is obtained, wherein:

[0033] The mixed salt solution is any one of sulfate, nitrate, hydrochloride and acetate of nickel, cobalt and manganese, and the molar ratio of nickel:cobalt:manganese is x:y:(1-xy), wherein 0.60≤x≤0.70, 0.02≤y≤0.30; the precipitant includes at least one of NaOH, KOH, LiOH and NaCO3, and the complexing agent includes at least one of ammonia water, sodium citrate, sodium oxalate and ammonium bicarbonate.

[0034] In an optional embodiment, the preparation of the base liquid includes the following steps: adding pure water to the reactor, introducing an inert gas to replace the air, and after the air in the reactor is replaced, stirring and heating are turned on, the pH value and ammonia concentration in the reactor are adjusted to the required values, and after the temperature reaches the required value, a dispersant and an amino carbon microsphere powder are added to the pure water in sequence, and stirred to uniformly disperse the dispersant and the amino carbon microsphere powder to obtain a base liquid, wherein:

[0035] The heating temperature in the reactor is controlled to be 40°C~80°C, the stirring rate is 200rpm~1200rpm, the pH in the reactor is adjusted to 10~13, the ammonia concentration is 0.1mol / L~2mol / L, the dispersant includes at least one of ethanol, n-butanol, ammonium citrate, sodium citrate, sodium hexametaphosphate, sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate, the dispersant concentration is 0.1mol / L-2mol / L, the D50 of the amino carbon microspheres is 0.2μm-0.8μm, and after the dispersant and the amino carbon microsphere powder are added to the pure water in the reactor in turn, the stirring time is controlled to be 0.5-2h, and the inert gas includes at least one of nitrogen and argon.

[0036] The ternary or quaternary precursors prepared by the traditional co-precipitation method are mostly solid spheres. The nucleation method of the traditional co-precipitation method is used. Since the newly generated nuclei after feeding have low particle size and poor crystal form, and are easy to agglomerate due to excessive surface free energy, and the direct nucleation method in the early stage of the co-precipitation method often leads to secondary sphere agglomeration and twinning. In order to improve the dispersion of the crystal nucleus, an embodiment of the present invention provides a method for preparing a hollow porous positive electrode material precursor, and proposes to solve the agglomeration problem by adding a dispersant.

[0037] Dispersant is an auxiliary agent that can enhance and improve the dispersibility of solid or liquid materials, and can promote the uniform dispersion of material particles in the medium. There are three dispersing mechanisms of dispersants: 1. Adsorbed on the surface of solid particles to reduce the interfacial tension between liquid-liquid or solid-liquid. Make the surface of condensed solid particles easy to wet; 2. Polymer dispersants form an adsorption layer on the surface of solid particles, increase the charge on the surface of solid particles, and increase the reaction force between particles that form steric hindrance; 3. Form a bilayer structure on the surface of solid particles, and the polar end of the outer dispersant has a strong affinity with water, which increases the degree of wetting of solid particles by water, and the solid particles are kept away from each other due to electrostatic repulsion. In this embodiment, the dispersant includes any one or more of ethanol, n-butanol, ammonium citrate, sodium citrate, sodium hexametaphosphate, sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate. The dispersing characteristics of the dispersant can make the precursor have better dispersibility.

[0038] At the same time, multiple experimental results show that the ammonia value of the reaction system has an important influence on the formation of the product: if the ammonia value of the reaction system during the preparation process exceeds the upper limit of the process requirements, the complexation is dominant, the nucleation is abnormal, the growth process does not form secondary particles, and no product is produced. If the ammonia value of the reaction system during the preparation process is lower than the lower limit of the process requirements, there will be no crystals after feeding, and the formed substance is fine flocs, some of which are not attached to the amino carbon microspheres, and the particle size is stagnant, and the target particle size cannot be reached, and no qualified products are produced.

[0039] In an optional embodiment, the preparation of the hollow porous cathode material precursor includes: mixing the reaction slurry and the hydroxylating agent solution, continuing to keep warm and stir in an inert gas atmosphere for 2h-5h, then centrifugally dehydrating, washing with dilute alkali and hot pure water respectively, and after drying, removing the internal template under high temperature conditions, taking out, screening, demagnetizing, and mixing to obtain a hollow porous cathode material precursor with good dispersibility and no adhesion, wherein:

[0040] The hydroxylating agent includes at least one of hydrogen peroxide and peracetic acid, the drying temperature is 100°C-180°C, the temperature for high-temperature removal of the internal template is 200°C-600°C, the time is 5h-10h, and the mass of the material in the reaction slurry: the mass of the hydroxylating agent is 10:1.

[0041] As can be seen from the above, an embodiment of the present invention also provides a method for preparing the above-mentioned hollow porous cathode material precursor, which includes: adding a dispersant to the bottom liquid in the reactor to improve the dispersibility of the hollow porous cathode material precursor and avoid agglomeration and twinning. Using amino carbon microspheres as templates, the amino functional group has a high electron donation effect and good nucleophilicity, which can act as a convenient linking base between the template and the metal ions, so that the salt solution is deposited on the template surface after feeding without additional nucleation. In addition, the template can support the hollow structure of the precursor, and compared with other hollow structure precursors, the structure is more stable and there will be no structural collapse problem. After the reaction is completed, a hydroxylating agent solution is added under the protection of an inert atmosphere for surface hydroxylation modification, which increases metal active sites, enhances lithium ion insertion and extraction, and improves discharge capacity and cycle performance.

[0042] In a third aspect, an embodiment of the present invention further provides a hollow porous positive electrode material, which is prepared by mixing the above hollow porous positive electrode material precursor or the hollow porous positive electrode material precursor prepared by the above preparation method with a lithium source and sintering.

[0043] In a fourth aspect, an embodiment of the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the above-mentioned hollow porous positive electrode material.

[0044] The present invention will be further described below in conjunction with the embodiments.

[0045] Example 1

[0046] A method for preparing a hollow porous positive electrode material precursor comprises the following steps:

[0047] (1) Preparation of mixed salt solution: First, nickel sulfate, cobalt sulfate and manganese sulfate were prepared with deionized water to prepare a mixed salt solution with a molar ratio of Ni:Co:Mn=0.60:0.10:0.30 and a concentration of 2.2 mol / L.

[0048] (2) Prepare precipitant solution: Use deionized water to prepare solid NaOH into a solution with a concentration of 8 mol / L.

[0049] (3) Prepare complexing agent solution: dilute the ammonia solution to 10 mol / L with deionized water.

[0050] (4) Prepare the hydroxylating agent solution: Use deionized water to prepare hydrogen peroxide into a solution with a concentration of 3 mol / L.

[0051] (5) Preparation of amino carbon microspheres: Commercially available carbon microsphere powder with a D50 of 0.8 μm is pre-treated with carboxylation using a mixed solution of concentrated nitric acid and concentrated sulfuric acid to obtain carboxylated carbon microsphere powder. The carboxylated carbon microsphere powder is then added to deionized water for ultrasonic treatment. Hexamethylenediamine and ammonia water are then added for reaction. The mixture is subjected to microwave irradiation. The mixture is then filtered, washed, and dried to obtain amino carbon microspheres.

[0052] (6) Preparation of base liquid: Prepare 20 L of base liquid in a 50 L reactor with temperature and stirring control. First, add pure water to the reactor and introduce inert gas to replace the air. After the air in the reactor is replaced, start the stirring and heating program and control the stirring speed to 500 rpm and the temperature to 45±0.5°C. Adjust the pH value in the reactor to 11.10 and the ammonia concentration to 0.5 mol / L. Then add 2.44 kg of dispersant sodium hexametaphosphate to make the concentration of the dispersant 0.2 mol / L. After stirring and dissolving evenly, continue to add amino carbon microsphere powder and stir at a stirring rate of 500 rpm for 2 h to make the amino carbon microsphere powder evenly dispersed in the base liquid.

[0053] (7) Depositing a composite metal hydroxide on the surface of the amino carbon microspheres to obtain a reaction slurry: continuously adding the aforementioned solutions (1), (2), and (3) to the bottom liquid in the reactor at a certain flow rate in proportion. Depending on the test results, the flow rates of the solutions (2) and (3) can be adjusted to maintain a stable reaction atmosphere. The reaction is continued until a primary product with a particle size of 3.5 μm-4.0 μm is obtained.

[0054] (8) Add the aforementioned (4) solution to the reaction slurry obtained by the coprecipitation reaction in a ratio of theoretical primary product weight: hydroxylating agent = 10:1 in the reactor, continue to keep warm and stir for 2 hours in a nitrogen atmosphere, then centrifuge and dehydrate the material, wash away Na and S in the material with dilute alkali and hot pure water respectively, and obtain a wet material precursor with qualified Na and S. After drying at 120°C, place it at high temperature for 5 hours to remove the amino carbon microspheres inside, then take it out, screen, demagnetize, and mix it to obtain a hollow porous positive electrode material precursor with good dispersibility, no adhesion, and many surface active sites. The product morphology and cross-section are shown in Figure 1 .

[0055] Comparative Example 1

[0056] A method for preparing a positive electrode material precursor with a solid structure, wherein no amino carbon microspheres are added to the base liquid, comprises the following steps:

[0057] (1) Preparation of mixed salt solution: First, nickel sulfate, cobalt sulfate and manganese sulfate were prepared with deionized water to prepare a mixed salt solution with a molar ratio of Ni:Co:Mn=0.60:0.10:0.30 and a concentration of 2.2 mol / L.

[0058] (2) Prepare precipitant solution: Use deionized water to prepare solid NaOH into a solution with a concentration of 8 mol / L.

[0059] (3) Prepare complexing agent solution: dilute the ammonia solution to 10 mol / L with deionized water.

[0060] (4) Prepare the hydroxylating agent solution: Use deionized water to prepare hydrogen peroxide into a solution with a concentration of 3 mol / L.

[0061] (5) Preparation of base liquid: Prepare 20 L of base liquid in a 50 L reactor with temperature and stirring control. First, add pure water to the reactor and introduce inert gas to replace the air. After the air in the reactor is replaced, start the stirring and heating program and control the stirring speed to 500 rpm and the temperature to 45 ± 0.5 °C. Adjust the pH value in the reactor to 11.10 and the ammonia concentration to 0.5 mol / L. Then, add 2.44 kg of dispersant sodium hexametaphosphate to make the concentration of the dispersant 0.2 mol / L, so that the dispersant is evenly dispersed in the base liquid.

[0062] (6) Depositing composite metal hydroxide to obtain reaction slurry: continuously adding the aforementioned solutions (1), (2) and (3) into the bottom liquid in the reactor at a certain flow rate in proportion. According to the test results, the flow rates of solutions (2) and (3) can be adjusted to stabilize the reaction atmosphere. The reaction is continued until a primary product with a particle size of 3.5 μm-4.0 μm is obtained.

[0063] (7) Add the above-mentioned (4) solution to the reaction slurry obtained by the coprecipitation reaction in a ratio of theoretical primary product weight: hydroxylating agent = 10:1 in the reactor, continue to keep warm and stir in a nitrogen atmosphere for 2 hours, then centrifuge and dehydrate the material, wash away Na and S in the material with dilute alkali and hot pure water respectively, and obtain a wet material precursor with qualified Na and S. After drying at 120°C, sieve, demagnetize, and mix the material to obtain a positive electrode material precursor with a solid structure that has good dispersibility, no adhesion, and many surface active sites. The product morphology and cross-section are shown in Figure 2 .

[0064] Comparative Example 2

[0065] A method for preparing a hollow porous cathode material precursor, wherein no dispersant is added to the base liquid, comprises the following steps:

[0066] (1) Preparation of mixed salt solution: First, nickel sulfate, cobalt sulfate and manganese sulfate were prepared with deionized water to prepare a mixed salt solution with a molar ratio of Ni:Co:Mn=0.60:0.10:0.30 and a concentration of 2.2 mol / L.

[0067] (2) Prepare precipitant solution: Use deionized water to prepare solid NaOH into a solution with a concentration of 8 mol / L.

[0068] (3) Prepare complexing agent solution: dilute the ammonia solution to 10 mol / L with deionized water.

[0069] (4) Prepare the hydroxylating agent solution: Use deionized water to prepare hydrogen peroxide into a solution with a concentration of 3 mol / L.

[0070] (5) Preparation of amino carbon microspheres: Commercially available carbon microsphere powder with a D50 of 0.8 μm is pre-treated with carboxylation using a mixed solution of concentrated nitric acid and concentrated sulfuric acid to obtain carboxylated carbon microsphere powder. The carboxylated carbon microsphere powder is then added to deionized water for ultrasonic treatment. Hexamethylenediamine and ammonia water are then added for reaction. The mixture is subjected to microwave irradiation. The mixture is then filtered, washed, and dried to obtain amino carbon microspheres.

[0071] (6) Preparation of base liquid: Prepare 20 L of base liquid in a 50 L reactor with temperature and stirring control. First, add pure water to the reactor and introduce inert gas to replace the air. After the air in the reactor is replaced, start the stirring and heating program and control the stirring speed to 500 rpm and the temperature to 45±0.5°C. Adjust the pH value in the reactor to 11.10 and the ammonia concentration to 0.5 mol / L. Then add the amino carbon microsphere powder and stir at a stirring rate of 500 rpm for 2 h to ensure that the amino carbon microsphere powder is evenly dispersed in the base liquid.

[0072] (7) Depositing composite metal hydroxide on the surface of amino carbon microspheres to obtain reaction slurry: continuously adding the aforementioned solutions (1), (2) and (3) into the bottom liquid in the reactor at a certain flow rate in proportion. According to the test results, the flow rates of solutions (2) and (3) can be adjusted to stabilize the reaction atmosphere. The reaction is continued until a primary product with a particle size of 3.5 μm-4.0 μm is obtained.

[0073] (8) Add the aforementioned (4) solution to the reaction slurry obtained by the coprecipitation reaction in a ratio of theoretical primary product weight: hydroxylating agent = 10:1 in the reactor, continue to keep warm and stir for 2 hours in a nitrogen atmosphere, then centrifuge and dehydrate the material, wash away Na and S in the material with dilute alkali and hot pure water respectively, and obtain a wet material precursor with qualified Na and S. After drying at 120°C, place it at high temperature for 5 hours to remove the amino carbon microspheres inside, then take it out, screen, demagnetize, and mix it to obtain a hollow porous positive electrode material precursor with many surface active sites. See the electron microscope and cross-sectional view of the product. Figure 3 .

[0074] Comparative Example 3

[0075] A method for preparing a hollow porous cathode material precursor without using a hydroxylating agent comprises the following steps:

[0076] (1) Prepare a mixed salt solution: First, nickel sulfate, cobalt sulfate, and manganese sulfate are prepared with deionized water to prepare a mixed salt solution with a molar ratio of Ni:Co:Mn=0.60:0.10:0.30 and a concentration of 2 mol / L.

[0077] (2) Prepare precipitant solution: Use deionized water to prepare solid NaOH into a solution with a concentration of 8 mol / L.

[0078] (3) Prepare complexing agent solution: dilute the ammonia solution to 10 mol / L with deionized water.

[0079] (4) Prepare the hydroxylating agent solution: Use deionized water to prepare hydrogen peroxide into a solution with a concentration of 3 mol / L.

[0080] (5) Preparation of amino carbon microspheres: Commercially available carbon microsphere powder with a D50 of 0.8 μm is pre-treated with carboxylation using a mixed solution of concentrated nitric acid and concentrated sulfuric acid to obtain carboxylated carbon microsphere powder. The carboxylated carbon microsphere powder is then added to deionized water for ultrasonic treatment. Hexamethylenediamine and ammonia water are then added for reaction. The mixture is subjected to microwave irradiation. The mixture is then filtered, washed, and dried to obtain amino carbon microspheres.

[0081] (6) Prepare the base liquid: Prepare 20L of base liquid in a 50L reactor with temperature and stirring control. First, add pure water to the reactor and introduce inert gas to replace the air. After the air in the reactor is replaced, start the stirring and heating program, control the stirring speed to 500rpm, the temperature to 45±0.5℃, adjust the pH value in the reactor to 11.10, and then add 2.44kg of dispersant sodium hexametaphosphate to make the concentration of the dispersant 0.2mol / L. After stirring and dissolving evenly, continue to add amino carbon microsphere powder and stir at a stirring rate of 500rpm for 2h to make the amino carbon microsphere powder evenly dispersed in the base liquid.

[0082] (7) Depositing composite metal hydroxide on the surface of amino carbon microspheres to obtain a reaction slurry: continuously adding the aforementioned (1), (2), and (3) solutions to the bottom liquid in the reactor at a certain flow rate in proportion. According to the test results, the flow rates of (2) and (3) solutions can be adjusted to stabilize the reaction atmosphere, and the reaction is continued until a primary product with a particle size of 3.5μm-4.0μm is obtained. The primary product is then centrifuged and dehydrated, and the Na and S in the material are washed away with dilute alkali and hot pure water, respectively, to obtain a wet material precursor with qualified Na and S. After drying at 120°C, it is placed under high temperature conditions for 5 hours to remove the amino carbon microspheres inside, and then taken out, sieved, demagnetized, and mixed to obtain a hollow porous positive electrode material precursor with good dispersion and no adhesion. The product morphology and cross-section are shown in Figure 4 .

[0083] SEM and cross-section analysis

[0084] Figure 1 The following is a scanning electron microscope image (left) and a scanning electron microscope cross-sectional image (right) of the product obtained in Example 1. Figure 1 As can be seen from the left figure in the figure, the secondary spheres of the precursor material prepared in Example 1 have regular morphology, good dispersibility, no adhesion and agglomeration of secondary spheres, uniform particle size distribution, and D50 is 3.843 μm. Figure 1 As can be seen from the right figure, the center of the secondary sphere is a hollow structure with a cavity diameter of about 0.8 μm, which is the diameter of the amino carbon microsphere.

[0085] Figure 2 The scanning electron microscope image (left) and the scanning electron microscope cross-sectional image (right) of the product obtained in Comparative Example 1 are compared with Example 1. When the product of Comparative Example 1 is prepared, no amino carbon microspheres are added to the base liquid. The secondary spherical morphology of the precursor material obtained under the same other conditions is similar to that of Example 1 (see Figure 2 ), by Figure 2 As can be seen from the right picture in , the center of the secondary sphere is a solid structure.

[0086] Figure 3 The scanning electron microscope image (left) and scanning electron microscope cross-sectional image (right) of the product obtained in comparative example 2 are shown. Compared with Example 1, no dispersant was added to the base liquid during the preparation of the product in comparative example 2. The secondary spheres of the precursor material obtained under the same other conditions were more severely agglomerated, and the adhesion between particles was more serious. The sintering of agglomerated particles is difficult to control, and the agglomerated particles will reduce the compaction density, thereby affecting the electrical performance. Similar to Example 1, there is a cavity structure with a diameter of 0.8 μm in the center of the secondary sphere, which is the diameter of the amino carbon microsphere.

[0087] Figure 4 The scanning electron microscope image (left) and scanning electron microscope cross-sectional image (right) of the product obtained in Comparative Example 3 are shown. Compared with Example 1, no hydroxylating agent was added after the reaction when the product of Comparative Example 3 was prepared. The primary particle morphology of the secondary sphere is thicker than that of Example 1, and the cross-sectional image also has a cavity structure with a diameter of 0.8 μm (see Figure 2 (right picture in the figure).

[0088] Performance Testing

[0089] The precursors prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were mixed with lithium hydroxide at a molar ratio of 1:1.05, sintered under the same conditions, and finally obtained four positive electrode materials after grinding and crushing, which were respectively recorded as A, A1, A2, and A3. They were made into positive button cells and the charge and discharge performance was tested.

[0090] Capacity retention rate after 100 cycles (%) = discharge capacity at the 100th cycle / discharge capacity at the 1st cycle × 100%, the discharge capacity and cycle retention rate of the material are obtained, as shown in the table below.

[0091] Table 1 Electrical properties of the positive electrode materials obtained in the examples and comparative examples

[0092] Serial number Cathode material name 0.1C discharge capacity mAh / g Capacity retention after 100 cycles Example 1 A 192.5 98.1% Comparative Example 1 A1 188.9 96.3% Comparative Example 2 A2 190.7 97.6% Comparative Example 3 A3 185.3 95.9%

[0093] As can be seen from Table 1, the hollow porous positive electrode material precursor prepared by the method provided in the embodiment of the present invention, the positive electrode material prepared by mixing it with a lithium source and sintering it as a positive electrode material for a lithium ion battery, its initial discharge capacity can reach 192.5mAh / g, which is greater than the initial discharge capacity of the positive electrode material prepared in the comparative example, and its capacity retention rate after 100 cycles can reach 98.1%. The electrical performance test results show that the scheme provided in the embodiment of the present invention can prepare a hollow porous positive electrode material precursor with good dispersibility, no agglomeration and many surface active sites. The hollow porous positive electrode material prepared by the above hollow porous positive electrode material precursor can inherit the advantages of the hollow porous positive electrode material precursor such as good dispersibility, good dispersibility, no adhesion, hollow inside and many shell active sites. The lithium ion battery composed of the above hollow porous positive electrode material has a higher discharge capacity and more stable cycle performance.

[0094] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hollow porous cathode material precursor, characterized in that: The method comprises the following steps: using amino carbon microspheres as templates, depositing composite metal hydroxides on the surfaces of the amino carbon microspheres to obtain a reaction slurry, then mixing the reaction slurry with a hydroxylation reagent solution for reaction, washing and drying, and removing the internal template at high temperature to obtain a hollow porous cathode material precursor, wherein the hollow porous cathode material precursor is a hollow porous microsphere, and the surface of the hollow porous microsphere contains hydroxyl groups.

2. The preparation method according to claim 1, characterized in that: The following steps are involved: A mixed salt solution, a precipitant solution and a complexing agent solution are added to a base liquid containing the amino carbon microspheres, and a composite metal hydroxide is deposited on the surface of the amino carbon microspheres to obtain a reaction slurry. The reaction slurry is then mixed with a hydroxylation agent solution for reaction. After centrifugal dehydration and drying, the internal template is removed by sintering to obtain a hollow porous positive electrode material precursor.

3. The preparation method according to claim 2, characterized in that: The preparation of the reaction slurry comprises: continuously and concurrently flowing a mixed salt solution, a precipitant solution and a complexing agent solution into a bottom solution, adjusting the flow rates of the precipitant solution and the complexing agent solution according to the test conditions to stabilize the reaction atmosphere, and continuously reacting until a reaction slurry with a required particle size is obtained, wherein: The mixed salt solution is any one of sulfate, nitrate, hydrochloride and acetate of nickel, cobalt and manganese, and the molar ratio of nickel:cobalt:manganese is x:y:(1-xy), wherein 0.60≤x≤0.70, 0.02≤y≤0.30; the precipitant includes at least one of NaOH, KOH, LiOH and NaCO3, and the complexing agent includes at least one of ammonia water, sodium citrate, sodium oxalate and ammonium bicarbonate.

4. The preparation method according to claim 3, characterized in that: Preparation of the base solution The method comprises the following steps: adding pure water to a reactor, introducing an inert gas to replace the air, and after the air in the reactor is completely replaced, stirring and heating are turned on, the pH value and ammonia concentration in the reactor are adjusted to the required values, and after the temperature reaches the required value, dispersant and amino carbon microsphere powder are added to the pure water in sequence, and stirred to uniformly disperse the dispersant and the amino carbon microsphere powder to obtain a base liquid, wherein: The heating temperature in the reactor is controlled to be 40°C~80°C, the stirring rate is 200rpm~1200rpm, the pH in the reactor is adjusted to 10~13, the ammonia concentration is 0.1mol / L~2mol / L, the dispersant includes at least one of ethanol, n-butanol, ammonium citrate, sodium citrate, sodium hexametaphosphate, sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate, the dispersant concentration is 0.1mol / L-2mol / L, the D50 of the amino carbon microspheres is 0.2μm-0.8μm, after the dispersant and the amino carbon microsphere powder are added to the pure water in the reactor in turn, the stirring time is controlled to be 0.5h-2h, and the inert gas includes at least one of nitrogen and argon.

5. The preparation method according to claim 2, characterized in that: The preparation of the hollow porous cathode material precursor comprises: mixing the reaction slurry and the hydroxylation reagent solution, continuing to heat and stir for 2h-5h in an inert gas atmosphere, then centrifugally dehydrating, washing with dilute alkali and hot pure water respectively, and after drying, removing the internal template under high temperature conditions, taking out, screening, demagnetizing, and mixing to obtain a hollow porous cathode material precursor with good dispersibility and no adhesion, wherein: The hydroxylation agent includes at least one of hydrogen peroxide and peracetic acid, the drying temperature is 100°C-180°C, the temperature for removing the internal template under high temperature conditions is 200°C-600°C, the time is 5h-10h, and the mass of the material in the reaction slurry: the mass of the hydroxylation agent is 10:

1.

6. The preparation method according to claim 1, characterized in that: The hollow core of the hollow porous positive electrode material precursor is a hollow spherical structure, and D50 is 0.2 μm-0.8 μm, and the thickness of the porous shell is 2.2 μm-3.8 μm.

7. The preparation method according to claim 6, characterized in that: The porosity of the porous shell is 10%-50%, and the mass of the porous shell containing hydroxyl groups accounts for 20%-60% of the total mass of the hollow porous positive electrode material precursor.

8. A hollow porous positive electrode material, characterized in that: The hollow porous positive electrode material precursor is prepared by mixing with a lithium source and sintering the mixture using the preparation method described in any one of claims 1 to 7.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the hollow porous positive electrode material according to claim 8.

Citation Information

Patent Citations

  • A kind of preparation method of water-based amino baking varnish

    CN116200086B

  • Preparation method of neodymium-doped lithium cobalt oxide composite positive electrode material clad with hydroxyl graphene

    CN104485453A

  • Preparation method of microsphere structure lithium ion battery cathode material

    CN106058176A